Have Improved Cookstoves Benefitted Rural Kenyans? : Findings from the EnDev Initiative - Samad, Hussain; Portale, Elisa (World Bank, Washington, DC, 2019)
Meeting the goal of universal access to clean cooking by 2030 remains a formidable challenge, as the current growth rate in clean-cooking coverage lags far behind the rate required to meet the goal (0.5 percent per year versus 3 percent). An estimated four billion US dollars in investment is needed to achieve universal access in twenty high-impact countries-125 times current spending of thirty-two million US dollars a year (SE4All 2018). Most of the twenty high-impact countries are in Africa and Asia.